I am the Truth. Michel Henry’s interpretation - Santasilia, Stefano (Razón y fe, 2025)
TThe question of truth is something that is simple only in appearance and, above all, only when it is assumed that the only criterion of truth can consist of the criterion of adaequatio. However, Christ’s affirmation in the Gospels, through which he presents himself as the truth, generates a problematic questioning of the authentic criterion of recognition of truth, imposing the need to think of “another possibility”. In this sense, Michel Henry’s proposal is presented as an interesting possibility of detecting another, more original modality of truth, capable of being in tune with the presentation that Christ makes of himself. This essay will try to show precisely how this proposal is developed, trying to synthetically indicate its problematic points and its possible advantages.
Keywords: truth; Christ; Michel Henry; Christology; phenomenon